2014
DOI: 10.1152/jn.00170.2014
|View full text |Cite
|
Sign up to set email alerts
|

Higher neuronal discharge rate in the motor area of the subthalamic nucleus of Parkinsonian patients

Abstract: In Parkinson's disease, pathological synchronous oscillations divide the subthalamic nucleus (STN) of patients into a dorsolateral oscillatory region and ventromedial nonoscillatory region. This bipartite division reflects the motor vs. the nonmotor (associative/limbic) subthalamic areas, respectively. However, significant topographic differences in the neuronal discharge rate between these two STN subregions in Parkinsonian patients is still controversial. In this study, 119 STN microelectrode trajectories (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 69 publications
1
28
1
Order By: Relevance
“…There are deviations in the number of detected SUs, in the percentage of US and rpv, as well as differences in the cluster quality measures. While the IS is typically used to select well isolated SUs [38,28,9] we here apply it to verify an augmented occurrence of well isolated SUs if the corresponding waveforms are distinct and thus easy to separate.…”
Section: Discussionmentioning
confidence: 99%
“…There are deviations in the number of detected SUs, in the percentage of US and rpv, as well as differences in the cluster quality measures. While the IS is typically used to select well isolated SUs [38,28,9] we here apply it to verify an augmented occurrence of well isolated SUs if the corresponding waveforms are distinct and thus easy to separate.…”
Section: Discussionmentioning
confidence: 99%
“…The recording of local field potentials (LFP) revealed that the most upper electrode contact of the quadripolar lead has the highest spectral power in the beta-frequency band (15–30 Hz, Figure 2A), indicating that it is located in the sensorimotor part of the STN (Figure 2A) (Holdefer et al, 2010; Yoshida et al, 2010; Zaidel et al, 2010; Novak et al, 2011; Deffains et al, 2014). Using this electrode contact as a reference, the neighboring contact revealed the most prominent phase synchronization when applying the Weighted Phase Lag Index (WPLI).…”
Section: Resultsmentioning
confidence: 99%
“…Recording stability was assessed (Deffains et al, 2014) and only stable recording segments longer than 10 s were used for further analyses. An automatic spike detection and sorting method was then used to isolate single units (Deffains et al, 2014) from the stable recording segments. An isolation score was calculated for each unit that was identified by the spike sorter software (Joshua et al, 2007).…”
Section: Offline Data Analysismentioning
confidence: 99%
“…Today, more than 25 years later, it is still the most widely accepted model linking dopamine imbalance in the striatum, rate of discharge in the nuclei of the basal ganglia and the motor expression of hypo-and hyper-kinetic movement disorders. Deep brain stimulation (DBS), a recognized treatment for both Dystonia and Parkinson's disease, allows researchers to test some of the predictions of this model in humans (Starr et al, 2005;Tang et al, 2007;Deffains et al, 2014).…”
Section: Introductionmentioning
confidence: 99%